Analysis of the Simple Additive Weighting Method in Educational Aid Decision Making (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Learning education aid is a government program aimed at assisting improverished children with high achievement incompleting their 12-year compulsory education by assisting them in gaining access to adequate educational resources. Everyschool undertakes screening processes to determine potential scholarship applicants. This selection is done to ensure that thestudents who receive this help are those who are eligible. Concerning the difficulties faced by the selection committee, such asthe difficulty in swiftly determining who is chosen as a candidate for aid receivers based on subjective or uncertain factors. Toovercome these problems, a decision support system was designed using the Simple Additive Weighting (SAW) method,which is a simple ranking method by finding a weighted sum based on predetermined assessment criteria. Total Income ofParents, Number of Dependents of Parents, Value of Report Cards, Personality, Achievements, Poor People, Number of AlphaStudent Attendances, and Received Government Program assistance were the criteria used. The goal of this research is todevelop a decision-making tool that will aid the school in selecting children who will receive assistance. The method used canget the first rank with 18.51 being the top average value.